The international migratory model of Spain. Changes and new challenges for the XXIst century - José Mª. Serrano Martínez (Belgeo)
Spain is a country that, within a few years, has experienced a drastic change in its migratory behaviour. It has passed from being an emigration country to one of immigration. But, in turn, the numbers of foreign residents in Spain do not fit a single immigration model. Several such models apply, relating to migrant origins and objectives. All this happens within the framework of a European panorama involving a substantial arrival of immigrants in countries which are economically mature but also dynamic in economic growth terms. These considerable immigration flows, of continuous growth, are occurring in a world context where the speed and ease of movement is increasing. For the future, it seems opportune to design sensible and reasonable immigration policies with a view to their likely relevance over the medium term.